Revisiting the effectiveness of HCHO/NO2 ratios for inferring ozone sensitivity to its precursors using high resolution airborne remote sensing observations in a high ozone episode during the KORUS-AQ campaign. (1st March 2020) - Souri, Amir H.; Nowlan, Caroline R.; Wolfe, Glenn M.; Lamsal, Lok N.; Chan Miller, Christopher E.; Abad, Gonzalo González; Janz, Scott J.; Fried, Alan; Blake, Donald R.; Weinheimer, Andrew J.; Diskin, Glenn S.; Liu, Xiong; et al.
Abstract: The nonlinear chemical processes involved in ozone production (P(O3 )) have necessitated using proxy indicators to convey information about the primary dependence of P(O3 ) on volatile organic compounds (VOCs) or nitrogen oxides (NOx ). In particular, the ratio of remotely sensed columns of formaldehyde (HCHO) to nitrogen dioxide (NO2 ) has been widely used for studying O3 sensitivity. Previous studies found that the errors in retrievals and the incoherent relationship between the column and the near-surface concentrations are a barrier in applying the ratio in a robust way. In addition to these obstacles, we provide calculational-observational evidence, using an ensemble of 0-D photochemical box models constrained by DC-8 aircraft measurements on an ozone event during the Korea-United States Air Quality (KORUS-AQ) campaign over Seoul, to demonstrate the chemical feedback of NO2 on the formation of HCHO is a controlling factor for the transition line between NOx -sensitive and NOx -saturated regimes. A fixed value ( 2.7) of the ratio of the chemical loss of NOx (LNOx ) to the chemical loss of HO2 +RO2 (LROx ) perceptibly differentiates the regimes. Following this value, data points with a ratio of HCHO/NO2 less than 1 can be safely classified as NOx -saturated regime, whereas points with ratios between 1 and 4 fall into one or the other regime. We attribute this mainly to the HCHO-NO2 chemical relationship causing the transition line to occur at larger (smaller) HCHO/NO2 ratios in VOC-rich (VOC-poor) environments. We then redefine the transition line to LNOx /LROx 2.7 that accounts for the HCHO-NO2 chemical relationship leading to HCHO = 3.7 × (NO2 – 1.14 × 10 16 molec.cm -2 ). Although the revised formula is locally calibrated (i.e., requires for readjustment for other regions), its mathematical format removes the need for having a wide range of thresholds used in HCHO/NO2 ratios that is a result of the chemical feedback. Therefore, to be able to properly take the chemical feedback into consideration, the use of HCHO = a × (NO2 – b) formula should be preferred to the ratio in future works. We then use the Geostationary Trace gas and Aerosol Sensor Optimization (GeoTASO) airborne instrument to study O3 sensitivity in Seoul. The unprecedented spatial (250 × 250 m 2 ) and temporal ( every 2 h) resolutions of HCHO and NO2 observations form the sensor enhance our understanding of P(O3 ) in Seoul; rather than providing a crude label for the entire city, more in-depth variabilities in chemical regimes are observed that should be able to inform mitigation strategies correspondingly. Highlights: Ozone sensitivity over Seoul on an exceptionally degraded air quality day. Various thresholds for HCHO/NO2 should be defined to label chemical regimes. The inherent dependence of HCHO production on NOx levels complicates the ratio. We redesign the formula to reflect the chemical feedback of NOx on HCHO. GeoTASO provides in-depth variabilities in chemical regimes over Seoul.